Effect of Job Dissatisfaction on Employee Turnover in the Palm Oil Industry of Malaysia - Ayesha, Noor; Yuserrie, Zainuddin (Penerbit Universiti Malaysia Pahang, 2015)
To date employee turnover is one of the most challenges facing by organizations. Several literatures are available on turnover crisis. It is a concern of researchers in Malaysian organizations. However, there are no literatures elsewhere for this issue in Palm Oil Industries. Therefore, in this study investigate this issue. It provides literature review related turnover crisis and a theoretical analysis of Mobely model (1977). In addition, this work is an outline of the employee dissatisfaction, leaving existing job and finding better opportunity. The Mobley’s model has been used to find out the turnover crisis which depends on employment factors.